In Vivo Effect of Different Doses of Silver Nanoparticles on the Seminiferous Tubules in Albino Rats: Histopathological Study - Ruqayah Salman; Abdulrahman Ali; Amenah Salman (Engineering and Technology Journal, 2020)
The study aims to investigate the effects of silver nanoparticles (Ag NPs) on the seminiferous tubules in Albino rats. Several in vitro studies have been performed in different cell models, using various nanoparticles. Pure and spherical AgNPs with an average size of 30 nm, was injected into two groups of male albino rats (6 rats for each group) in different doses. Histopathological changes in testis tissues were showed a harmful effect of the silver nanoparticles, manifested by reducing the number of spermatogenic cells, and a decrease in the number of leyidg´s cells (group 1), and hypotrophy in seminiferous and enlargement in interstitial spaces in group 2.